Acceptability of tranvia as a primary transportation within Intramuros and peripheries - Bulacan, Mary Joy G.; De Guzman, Andrea Kaye T.; Gonzales, Rheanna Anne; Pena,Jerry Francis T.; Velasco, Sophia Ashley V. (Manila : National University, 2024)
The study explores the acceptability of Travia as a primary mode of Transportation for various stakeholders in the historically and culturally significant area of Intramuros in Manila, Philippines.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Results and discussion -- Chapter 5. Summary, Conclusion and recommendation -- References -- Appendices.
Includes bibliographical references.